Pelindungan Hukum Atas Data Pribadi Anak dalam Sistem Elektronik: Perspektif UU No. 27 Tahun 2022 Tentang Pelindungan Data Pribadi dan Global - Endik Wahyudi; Donny Rifqi Miftahqul Huda (Laskar Karya, 2025)
The use of the internet has become an integral part of modern life. Internet users are not limited to adults but also include children, who generally lack mental maturity. Their online activities leave various digital footprints in the form of data, which can be exploited by irresponsible parties. Without adequate protection, such data may be misused and pose threats to children's privacy and security. In response to this issue, the Indonesian government enacted Law No. 27 of 2022 on Personal Data Protection (PDP Law), aimed at protecting the personal data of Indonesian citizens. However, the PDP Law still falls short in offering sufficient protection for children's personal data. When compared to similar regulations in other countries, the PDP Law reveals several weaknesses—particularly in its definitions, which are supposed to provide clarity for the public. This study aims to analyze the shortcomings of the PDP Law concerning children’s data protection and to compare it with international legal frameworks. This research employs a normative legal method. The findings indicate that the PDP Law lacks clarity regarding the protection of children's personal data and contains legal gaps in regulating its processing.